The determinants of work position among Gen X : a case of UiTM graduates / Rohani Mohd … [et al.] - Mohd, Rohani; Abdullah, Nazlinda; Shuib, Adibah; Ishar, Nor Irvoni; Abdul Rahim, Hasyimah; Noranee, Shereen (Universiti Teknologi Mara Selangor, 2016)
The purpose of this preliminary research is to identify corporate talents’ positioning of the UiTM graduates especially the Generation X, within the industries. At the same time, there is also the need to ascertain the factors that contributed to the success of the UiTM Generation X graduates. Majority of the research which have been conducted on the graduates involved the employability rate. However, none has been carried out in identifying the graduates’ career accomplishment. The sample of this research consisted of 191 UiTM graduates who are born between 1965 until 1985 (known as the Generation X). The responses were obtained via an online survey sent to random groups in UiTM emails. In addition, Facebook was also used as a medium in dissemininating the survey forms to random individuals whom has connections with the Generation X alumni. Rasch Measurement Model was employed by using the software WINSTEP 3.72.3, to measure the reliability and validity of the instrument. SPSS version 21 was used to answer the research objective of the study. The result has produced a fair person reliability at +0.66 while the Cronbach Alpha reliability value was at 0.72 and an excellent item reliability of 0.99. In terms of career positioning, 60% of the Generation- falls within the middle management position. This reflects the success of the Gen-X where most of them were able to obtain posts like lecturers, engineers and managers. As for the factors which contributed to the success of the alumni, it was found that involvement in clubs, soft skills and orientation towards religion play important roles in determining the career position of GenX. These findings validate past research and demonstrate that the pattern continues into the present. Surprisingly, it was found that academic achievement, hard skills and personality traits hardly had any influence on the career positions of the Gen-X. It was also discovered that the success of the Gen-X could be due to other factors which is beyond the horizon of this research. Therefore, it was recommended that students should be encouraged to be actively involved in clubs. This must be balanced with religious values exposure so that they know the limit of their involvement.